Engineering carbon nanocomposites for energy storage and conversion - Tian, Hao (Curtin University, 2017)
Carbon nanocomposites have been successfully developed and applied in the field of energy storage and conversion such as supercapacitors and lithium ion batteries. The effects of controlled morphologies and structures have been fundamentally studied to enhance the electrochemical performance. The aim of this thesis is to develop facile and effective methods to prepare carbon nanocomposites with appropriate morphologies, compositions, porosities and functionalities to suit their application in energy storage and conversion.